Paraoxonase1 Genetic Polymorphisms in a Mixed Ancestry African Population - Macharia, M.; Kengne, A. P.; Blackhurst, D. M.; Erasmus, R. T.; Matsha, T. E. (Mediators of Inflammation, 2014)
Paraoxonase 1 (PON1) activity is markedly influenced by coding polymorphisms, Q/R at position 192 and M/L at position 55 of the PON1 gene. We investigated the frequencies of these polymorphisms and their effects on PON1 and antioxidant activities in 844 South African mixed ancestry individuals. Genotyping was done using allele-specific TaqMan technology, PON1 activities were measured using paraoxon and phenylacetate, oxidative status was determined by measuring the antioxidant activities of ferric reducing antioxidant power and trolox equivalent antioxidant capacity, and lipid peroxidation markers included malondialdehyde and oxidized LDL. The frequencies of Q192R and L55M were 47.6% and 28.8%, respectively, and the most common corresponding alleles were 192R (60.4%) and 55M (82.6%). The Q192 was significantly associated with 5.8 units’ increase in PON1 concentration and 15.4 units’ decrease in PONase activity after adjustment for age, sex, BMI, and diabetes, with suggestion of differential effects by diabetes status. The PON1 L55 variant was associated with none of the measured indices. In conclusion, we have shown that the Q192R polymorphism is a determinant of both PON1 concentration and activity and this association appeared to be enhanced in subjects with diabetes.